Political Parties and Democracy: Are Political Parties Still the Main Pillar in the Democratization of the Indonesian Government? - Leli Salman Al-Farisi (Public Policy: Jurnal Ilmu Sosial dan Kebijakan, 2025)
Theoretically and normatively, Political Parties are articulate organizations that are channels for the interests of the community to be fought for to become state policies. Democracy, with all its attributes, will not exist without the presence of Political Parties. Therefore, Political Parties must be able to build an effective and stable Indonesian Democracy, but in practice the personalization of Political Parties is increasingly strengthening, which gives rise to the latent danger of ideological fragmentation, hegemony and internal conflict. This condition has justified the assumption that Political Parties, which are de jure the main pillars of democracy, but de facto have no contribution to the Democratization of Government.